2017
DOI: 10.1680/jbibn.16.00010
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetics and its tools

Abstract: Biomimetics, as the transfer of strategies from biology to technology, is an emerging research area and has led to significant concepts over the past decades. The development of such concepts is described by the process of biomimetics, encompassing several steps. In Practice, beneficiaries of the process face challenges. Therefore, to overcome challenges and to facilitate the steps, tools have been developed in various areas, such as engineering, computing and design. However, these tools are not widely used y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 57 publications
(57 reference statements)
0
82
0
2
Order By: Relevance
“…The connection of biomimicry to sustainability is inherent, as the evolutionary process of nature creates resource efficient results which should support the solution of ecological challenges caused by mankind 47,48 . Cohen and Reich 49 generated an overview of terminology of different biomimetic design directions.…”
Section: Biomimicrymentioning
confidence: 99%
“…The connection of biomimicry to sustainability is inherent, as the evolutionary process of nature creates resource efficient results which should support the solution of ecological challenges caused by mankind 47,48 . Cohen and Reich 49 generated an overview of terminology of different biomimetic design directions.…”
Section: Biomimicrymentioning
confidence: 99%
“…This increases the accessibility of biological information to practitioners with varying biological knowledge, but also allows for more efficient communication with a biologist, which we believe is a necessary endeavor to understand the complexity of biological systems. A recent review [8] identified The functional approach has long been a key central concept to the practice of biomimicry and has been identified as a solution to overcome the difficulties of its interdisciplinary nature. A recent review of biomimetic tools and processes identified several models of the problem-driven approach and correlated them with the general problem-solving process of Massay & Wallace 1956 [13], commonly used in engineering and design [12].…”
Section: Figurementioning
confidence: 99%
“…to engage in a collaborative process that transcends disciplinary boundaries, while also requiring knowledge transfer and communication across such disciplines. To add to this challenge, the tools created to facilitate biomimicry practice tend to be defined by one field of knowledge, primarily that of the tool developer [8]. For example, engineers tend to take a functional approach to problem decomposition while biologists more commonly tend to decompose the complex interactions within biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…VELCRO ® , an adhesive system inspired by how burrs cling to animal fur, is an example of biomimicry [2]. Despite biomimicry's potential to deliver disruptive product innovations [3,4], and excellent reviews of existing methods and associated tools [5,6], little has been published on best practices apart from a few studies carried out with students in classroom settings [7][8][9][10][11][12][13][14][15][16][17]. Notably absent in the literature are industry field studies designed to support and inform development of procedural scaffolding for the industry practice of biomimicry.…”
Section: Introductionmentioning
confidence: 99%